ANALISIS KEPUASAN PELANGGAN LAZADA DI JAKARTA SELATAN - Angie Rindani Ekaputri (2021)
The current Covid-19 has resulted in changes in transaction activities from offline to online. E-commerce users have also increased. However, there is one e-commerce that has actually experienced a decline. This research is a quantitative study which aims to determine the effect of each online convenience, online security, online trust on customer satisfaction. The population of this study is the people in South Jakarta who used Lazada marketplace application. The sample collection technique used was non probability sampling with purposive sampling type. Sources of data obtained through distributing questionnaires to 75 respondents. The analytical tool used in this research is SmartPLS3.0. The results obtained from this study are (1) online convenience has a significant effect on costumer satisfaction with a coefficient value of 0.267. (2) online security has no significant effect on costumer satisfaction with a coefficient value of 0.055. (3) online trust has a significant effect on costumer satisfaction with a coefficient value of 0.53. with adjusted R Square 0.622 or 62.2%.